Pemberdayaan Masyarakat Melalui Teknologi Informasi: Optimalisasi Jaringan 4G dan Pengembangan Website E-Government untuk Promosi Wisata Kampung Tambung, Kepulauan Sangihe - Israel, Ella Helmy; Papuas, Alfrianus; Maluenseng, Jackried Kanselir; Sehang, Steve Arthur (Civiliza Publishing, 2025)
Tambung village in the Sangihe Islands, Indonesia, has potential for beach tourism but is hindered by unstable internet connectivity and the lack of a digital promotion system, which hampers e-government implementation and tourism development. This community empowerment activity aims to optimize the internet network through the installation of a 4G GSM repeater and develop an e-government-based tourism promotion website. The implementation method includes problem identification using the USG (Urgency, Seriousness, Growth) scoring system, where the unstable internet network is the top priority (score 15). The solution implemented consisted of installing a repeater for 500-meter coverage and creating an integrated website that features tourist information, visual galleries, public service e-forms, and social media integration. Evaluation using a partner satisfaction questionnaire showed significant improvements in internet availability (+2.7), access to tourist information (+2.3), promotional effectiveness (+2.5), and public service quality (+2.0). Tourist visits increased by 40% in the three months post-implementation. This activity successfully built the foundation of digital services and effective tourism promotion, supporting digital village governance and sustainable tourism destination development. Integration with national platforms and mobile application development are recommended as the next steps.